Cost-Effectiveness of First-Line Versus Second-Line Pembrolizumab or Chemotherapy in Patients With Microsatellite-Instability-High/Mismatch Repair-Deficient Advanced Colorectal Cancer - Chongqing, Tan; Sini, Li; Xiaohui, Zeng; Liubao, Peng; Ye, Peng; Shuxia, Qin; Liting, Wang; Meiyu, Wu; Xiaomin, Wan (Frontiers in Pharmacology, 2021)
Background: Pembrolizumab is a guideline-recommended, both first- and second-line treatment option for microsatellite-instability-high (MSI-H)/mismatch repair-deficient (dMMR)advanced colorectal cancer patients. The aim of the present study is to investigates the health and economic outcomes of three treatment strategies with or without pembrolizumab in MSI-H/dMMR advanced colorectal cancer to define the best treatment strategy from the perspective of the US payer. Methods: A microsimulation model was developed to estimate the cost and effectiveness of three treatment strategies: 1) pembrolizumab used as first-line, 2) pembrolizumab used as second-line and, 3) chemotherapy. Life years (LYs), quality-adjusted LYs (QALYs) and lifetime costs were estimated. Results: The model projected that patients receiving pembrolizumab in the first-line setting gained 5.579 QALYs; this value was 1.501 and 3.941 QALYs more than that for patients receiving pembrolizumab in the second-line setting and chemotherapy, respectively. First-line pembrolizumab strategy dominated second-line pembrolizumab strategy. Compared with chemotherapy, first-line pembrolizumab strategy yielded an incremental cost of 50613.7, which resulted in an ICER of 13441 per QALY. Conclusion: For patients with MSI-H/dMMR advanced colorectal cancer, reserving pembrolizumab for second-line line use is dominated by its first-line use, and first-line use of pembrolizumab is cost-effective compared with chemotherapy.